الآليات الحجاجية البلاغية في شعر أحمد مطر نماذج مختارة - مومن بكوش, محدة, سلاف الجبارية; زنينة, شيماء (Univercty of Eloued, 2020)
Al-Hajjaj is a mechanism linked to texts whose aim is influence and persuasion, through which the speaker reaches his informative goal, as the subject of the study deals with: “The rhetorical pilgrimage mechanisms in selected examples of Ahmad Matar’s poetry,” which is a topic that delves into the study of this poetry and the arguments and rhetorical mechanisms it contains to influence receiver. Thus, a research plan was prepared consisting of an introduction, two chapters and a conclusion, the first chapter in which we tried to investigate the identity of the pilgrims and by studying its history with the Arabs and the West and touching on the types of pilgrims and the pilgrim mechanisms, and the second is the application side, which included the rhetorical pilgrim mechanisms in Ahmad Matar’s poetry in which we dealt with the pilgrims Knowing the meanings, the bad and the statement, and in the end the research concluded with a conclusion that represented the most important findings reached. In the end, we concluded that Ahmad Matar's poetry has a prominent role in persuading and influencing the recipient.
Keywords: الحجاج آليات الحجاج